Persepsi dan sikap masyarakat terhadap perlindungan dan pengelolaan mangrove di Kecamatan Sungai Apit Kabupaten Siak - Fatonah, Siti; Hamidy, Rasoel; Mulyadi, Aras; Efriyeldi, Efriyeldi (Universitas Riau, 2022)
Mangrove forest in Sungai Apit Sub District, Siak District, Riau is one of the mangrove ecosystems in Riau Province which has experienced a reduction in land area and is the widest in Siak Regency. This study aims to determine the perceptions and attitudes of the community in the protection and management of mangroves. The research was conducted in three villages in Sungai Apit Sub District, namely Rawa Mekar Jaya, Sungai Rawa and Mengkapan. Data was collected through observation and interviews with the community using mangroves. The results showed that the perception of the community in Sungai Apit towards the function and management of mangroves is classified as very good, while the attitude of the community towards the protection and management of mangroves is classified as good. The perception and attitude of the people of Rawa Mekar Jaya and Meng Kapan are better than the people of Sungai Rawa. Community involvement in rehabilitation activities is generally only at the time of the project and due to wages. The community has a high awareness of utilizing mangrove resources in a sustainable manner. The community has a high awareness of the protection and management of mangroves, but their involvement in rehabilitation activities requires money to compensate for the time and energy used. Therefore, alternative activities are needed that can increase funding sources and increase funding sources in local institutions related to mangroves.